M1 Macrophage Derived Exosomes Aggravate Experimental Autoimmune Neuritis via Modulating Th1 Response - Du, Tong; Yang, Chun-Lin; Ge, Meng-Ru; Liu, Ying; Zhang, Peng; Li, Heng; Li, Xiao-Li; Li, Tao; Liu, Yu-Dong; Dou, Ying-Chun; Yang, Bing; Duan, Rui-Sheng (Frontiers in Immunology, 2020)
Guillain-Barré syndrome (GBS), an immune-mediated disorder affecting the peripheral nervous system, is the most common and severe acute paralytic neuropathy. GBS remains to be potentially life-threatening and disabling despite the increasing availability of current standard therapeutic regimens. Therefore, more targeted therapeutics are in urgent need. Macrophages have been implicated in both initiation and resolution of experimental autoimmune neuritis (EAN), the animal model of GBS, but the exact mechanisms remain to be elucidated. It has been increasingly appreciated that exosomes, a type of extracellular vesicles (EVs), are of importance for functions of macrophages. Nevertheless, the roles of macrophage derived exosomes in EAN/GBS remain unclear. Here we determined the effects of macrophage derived exosomes on the development of EAN in Lewis rats. M1 macrophage derived exosomes (M1 exosomes) were found to aggravate EAN via boosting Th1 and Th17 response, while M2 macrophage derived exosomes (M2 exosomes) showed potentials to mitigate disease severity via a mechanism bypassing Th1 and Th17 response. Besides, both M1 and M2 exosomes increased germinal center reactions in EAN. Further in vitro studies confirmed that M1 exosomes could directly promote IFN-γ production in T cells and M2 exosomes were not capable of inhibiting IFN-γ expression. Thus, our data identify a previously undescribed means that M1 macrophages amplify Th1 response via exosomes and provide novel insights into the crosstalk between macrophages and T cells as well.2